The spontaneous co-creation of comedy: Humour in improvised theatrical fiction - Landert, Daniela (Journal of pragmatics, 2021)
This study investigates humour strategies in improvised theatrical fiction. Improvised theatre is a type of data that has thus far remained unexplored by linguistic studies, but which provides interesting insight into the characteristics of fictional texts and, more specifically, into the relation between dialogues in fiction and dialogues in spontaneous conversation. The starting point for the analysis is the participation framework of improvised theatre, which is compared to the well-studied participation framework of telecinematic discourse. The comparison of the two types of data identifies a number of crucial differences between their participation frameworks, such as the co-presence of the audience during text creation, an emphasis on the production process, and the temporal proximity between text production and reception. These differences form the background of the discussion of three humour strategies that are typical of improvised theatrical fiction, namely metafictional frame breaking, non-contrived humour and the co-construction of humorous exchanges. The analysis shows that these strategies are closely related to the characteristics of the communicative framework that set improvised theatrical fiction apart from scripted fiction, such as telecinematic discourse. This demonstrates that humour strategies are dependent on the communicative framework of the text type in which they are used.
Gesehen am 04.04.2024